The chronic challenge - new vistas on long-term multisite contacts to the central nervous system - Ulrich G. Hofmann (Frontiers Research Topics, 2015)
Have you ever heard of a Hype-Cycle? It is a description that was put forward by an IT consultancy firm to describe certain phenomena that happen within the life cycle of new technology products. As Fenn and Raskino stated in their book (Fenn and Raskino 2008), a novel technology - a - "Technology Trigger" - gives rise to a steep increase in interest, leading to the "Peak of Inflated Expectations". Following an accumulation of more detailed knowledge on the technology and its short-comings, the stake holders may need to traverse a "Trough of Disillusionment", which is followed by a shallower "Slope of Enlightenment", before finally reaching the "Plateau of Productivity". In spite of the limitations and criticisms levied on this over-simplified description of a technology's life-cycle, it is nonetheless able to describe well the situation we are all experiencing within the brain-machine-interfacing community. Our technology trigger was the development of batch-processed multisite neuronal interfaces based on silicon during the 1980s and 1990s (Sangler and Wise 1990, Campbell, Jones et al. 1991, Wise and Najafi 1991, Rousche and Normann 1992, Nordhausen, Maynard et al. 1996). This gave rise to a seemingly exponential growth of knowledge within the neurosciences, leading to the expectation of thought-controlled devices and prostheses for handicapped people in the very near future (Chapin, Moxon et al. 1999, Wessberg, Stambaugh et al. 2000, Chapin and Moxon 2001, Serruya, Hatsopoulos et al. 2002). Unfortunately, whereas significant steps towards artificial robotic limbs could have been implemented during the last decade (Johannes, Bigelow et al. 2011, Oung, Pohl et al. 2012, Belter, Segil et al. 2013), direct invasive intracortical interfacing was not quite able to keep up with these expectations. Insofar, we are currently facing the challenging, but tedious walk through the Trough of Disillusionment. Undoubtedly, more than two decades of intense research on brain-machine-interfaces (BMI's) have produced a tremendous wealth of information towards the ultimate goal: a clinically useful cortical prosthesis. Unfortunately even today - after huge fiscal efforts - the goal seems almost to be as far away as it was when it was originally put forward. At the very least, we have to state that one of the main challenges towards a clinical useful BMI has not been sufficiently answered yet: regarding the long term - or even truly chronic - stability of the neural cortical interface, as well as the signals it has to provide over a significant fraction of a human's lifespan. Even the recently demonstrated advances in BMI's in both humans and non-human primates have to deal with a severe decay of spiking activity that occurs over weeks and months (Chestek, Gilja et al. 2011, Hochberg, Bacher et al. 2012, Collinger, Kryger et al. 2014, Nuyujukian, Kao et al. 2014, Stavisky, Kao et al. 2014, Wodlinger, Downey et al. 2014) and resolve to simplified features to keep a brain-derived communication channel open (Christie, Tat et al. 2014).